2010
DOI: 10.1021/ie100352p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model of the Dehydrogenation of Methylcyclohexane over Monometallic and Bimetallic Pt Catalysts

Abstract: Various kinetic models were developed for methylcyclohexane (MCH) dehydrogenation over supported Pt catalysts. The best fitting mechanistic model is of the non-Langmuirian/noncompetitive Horiuti-Polanyi type. In this model, the Horiuti-Polanyi aromatic hydrogenation mechanism, which assumes an atomic hydrogen addition to aromatics on the catalyst surface, is applied in reverse to MCH dehydrogenation. The model also assumes that hydrogen and MCH molecules adsorb noncompetitively on two different types of sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…Due to the high intrinsic hydrogenation/dehydrogenation activity, the conventional Pt-based catalysts are currently used for the methylcyclohexane dehydrogenation, such as Pt/Al 2 O 3 , Pt/V 2 O 5 , Pt/Y 2 O 3 and Pt-Re/Al 2 O 3 [8][9][10][11][12][13][14][15][16][17][18]. But the scarcity and the high cost of the noble metals prompted researchers to find alternatives, and thus, various transition metals have recently been tested in cycloalkanes dehydrogenation such as Ni, Cu, Sn [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high intrinsic hydrogenation/dehydrogenation activity, the conventional Pt-based catalysts are currently used for the methylcyclohexane dehydrogenation, such as Pt/Al 2 O 3 , Pt/V 2 O 5 , Pt/Y 2 O 3 and Pt-Re/Al 2 O 3 [8][9][10][11][12][13][14][15][16][17][18]. But the scarcity and the high cost of the noble metals prompted researchers to find alternatives, and thus, various transition metals have recently been tested in cycloalkanes dehydrogenation such as Ni, Cu, Sn [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Re/Al 2 O 3 catalyst, Pal et al[30] found a value of 56.4 kJ mol -1 on the same catalyst as that of Jothimurugesan et al[25], Tsakiris[19] reported apparent activation energy values in the range of 44.1 - 60.0 kJ mol -1 for his Pt over α-and γ-alumina catalysts and for 0.3 wt% Pt/α-Al 2 O 3 and 1.0 wt% Pt/-Al 2 O 3 , activation energies were 45.7 and 49.8 kJ mol -1 , respectively, Alhumaidan et al[20] used a value of 55.4 kJ mol -1 as the activation energy for the kinetic study of all of his commercial and in-house Pt/Al 2 O 3 catalysts, and Usman et al[7] have found activation energies of 50.2 for their work on 1.0 wt% Pt/θ-Al 2 O 3 .…”
mentioning
confidence: 84%
“…The above mentioned storage density does not take into account the total system volume (e.g. [21][22][23] More recently, polycyclic LOHCs with a nitrogen heteroatom have been proposed with the N-functionality causing much milder dehydrogenation conditions. The search for suitable LOHC compounds and mixtures thereof is 60 continued, since some of the components (e.g.…”
Section: Liquid Organic Hydrogen Carrier (Lohc) Systemsmentioning
confidence: 99%